Implementation of the dental prosthesis service in basic attention: experience report - Manoella Bastos Sousa Castelo Branco, Giovanni Telmo Leal Mesquita, Suyá Moura Mendes Alencar, Lúcia de fátima amorim rodrigues, Teresinha Soares Pereira Lopes (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/2238-7234.8esp14-18